Fundamentals of linear electronics : intergrated and discrete - Cox, James F., 1945- (Albany : Delmar, 1998)
This book is about: Diodes; Special Diodes; The bipolar transistor; Transistor circuits; ...
Keywords: Linear integrated circuits; Linear integrated circuits